Developing a System of Quality Assurance and Academic Accreditation System for Yemeni Universities in the Light of relevant International Experiences - Al- Sharjabi, Abdulrahman Mohammed; Al- Matari, Sameera Saleh; Al- Shibani, Mohammed Ali (Journal of Educational and Psychological Sciences, 2022)
This research aims to develop quality assurance and academic accreditation system for Yemeni universities based on relevant practice and experience of other countries. The researchers used descriptive analytical research in which the documentation on the quality assurance and academic accreditation practices of the Yemeni universities compared with the existing international practices documented in the available literature studies. The researchers used quality assurance and accreditation systems of the United Kingdom, France, and Holland, United States of America. Accordingly, the researchers proposed a quality assurance and accreditation system for Yemeni universities. The system consists of six areas such as funding, dissemination of quality and accreditation culture, infrastructure, lecturer, programs and syllabus, and scientific research. At the end of the research, the researchers suggested number of recommendation to provide suitable materialistic, human and financial to implement the quality assurance and academic accreditation system; independent structure from Ministry of higher education, focus on output and connect it with community needs and labor market, update periodically the standards in line with international experiences, in addition to complementary research in the subject of the research.